1999
DOI: 10.1207/s15327914nc352_9
|View full text |Cite
|
Sign up to set email alerts
|

A Probiotic Strain of L. Acidophilus Reduces DMH-Induced Large Intestinal Tumors in Male Sprague-Dawley Rats

Abstract: Probiotic bacteria strains were examined for their influence on 1,2-dimethylhydrazine (DMH)-induced intestinal tumors in 100 male Sprague-Dawley rats. Lactobacillus acidophilus (Delvo Pro LA-1), Lactobacillus rhamnosus (GG), Bifidobacterium animalis (CSCC1941), and Streptococcus thermophilus (DD145) strains were examined for their influence when added as freeze-dried bacteria to an experimental diet based on a high-fat semipurified (AIN-93) rodent diet. Four bacterial treatments were compared: L. acidophilus, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
65
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(67 citation statements)
references
References 22 publications
(21 reference statements)
1
65
0
1
Order By: Relevance
“…In addition, immunomodulation studies performed on HT29 cells showed that EF-Tu recombinant protein can induce a proinflammatory response in the presence of soluble CD14. Our in vitro results indicate that EF-Tu, through its binding to the intestinal mucosa, might participate in gut homeostasis.Probiotic bacteria, mainly lactic acid bacteria and bifidobacteria, have been shown to have beneficial effects on the immune defenses and to alleviate or prevent diverse intestinal disorders (3,4,16,25,27,30,39,42,47). Several in vitro studies have shown that one of them, Lactobacillus johnsonii NCC533 (La1), is able to bind to epithelial cell lines (5,8,9,21) and can induce the secretion of different cytokines in coculture systems (9, 24).…”
mentioning
confidence: 99%
“…In addition, immunomodulation studies performed on HT29 cells showed that EF-Tu recombinant protein can induce a proinflammatory response in the presence of soluble CD14. Our in vitro results indicate that EF-Tu, through its binding to the intestinal mucosa, might participate in gut homeostasis.Probiotic bacteria, mainly lactic acid bacteria and bifidobacteria, have been shown to have beneficial effects on the immune defenses and to alleviate or prevent diverse intestinal disorders (3,4,16,25,27,30,39,42,47). Several in vitro studies have shown that one of them, Lactobacillus johnsonii NCC533 (La1), is able to bind to epithelial cell lines (5,8,9,21) and can induce the secretion of different cytokines in coculture systems (9, 24).…”
mentioning
confidence: 99%
“…23) Similar results have been observed in the colons of rats or mice treated with other probiotics administered during the post-initiation phase of DMH-induced carcinogenesis. [24][25][26] Abdelali et al (1995) determined that rats administered the colon carcinogen, DMH, and fed on diets containing 6ϫ10 9 cfu/d of Bifidobacterium longum evidenced a 63% reduction in the total number of aberrant crypts per colon, relative to a control diet containing no bifidobacteria. 24) As DNA damage has been implicated as the initial step in chemical carcinogenesis, the blocking of DNA damage should constitute the first line of defense against cancer induced by carcinogens.…”
Section: Discussionmentioning
confidence: 99%
“…In animal models, lactobacillus has been shown to bind dietary carcinogens [38] and decrease development of tumors in the colon after carcinogen challenge [39,40]. Preliminary research also suggests that lactobacilli, especially L. plantarum, can reduce the severity of chemotherapy-induced enterocolitis [41].…”
Section: Lactobacillus Speciesmentioning
confidence: 99%